SOCIOLINGUISTICS IN THE 21ST CENTURY: CHALLENGES AND CURRENT ISSUES - Mohinisokhon Akhatova Hasan's daughter (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Relevance of the topic. Sociolinguistics, as the study of the interaction between language and society, has traditionally examined how social variables such as class, gender, and region shape linguistic practices. However, the 21st century presents new and complex challenges that extend beyond classical concerns.In this context, modern sociolinguistics must expand its scope to address the realities of globalization and digitalization. The field now focuses not only on describing variation but also on understanding how language policies, technological innovations, and social inequalities shape linguistic practices in contemporary society.